THE ROLE OF POLITICAL PARTIES IN COMMUNITY POLITICAL EDUCATION - Yayang Nurafiat; Aan Anwar Sihabudin; Agus Nurulsyam Suparman (Faculty of Social And Political Science Universitas Galuh, 2022)
Political parties have a role in carrying out the functions of political parties by Law Number 2 of 2008 concerning political parties, one of which is to collect aspirations and provide political education for the community. This research is motivated by cooperation between political party administrators that have not been established, the ability to carry out political education that has not been active, and the absence of attitudes that can be used as role models from party administrators so that researchers are interested in researching the role of political parties in providing political education for the community. Sukahurip Village, Cisaga District, Ciamis Regency. This study uses a qualitative method with descriptive research that aims to describe the role of political parties in political education in society. Data collection was done by observation, literature study, and interviews, so the data used were primary data and secondary data. The data analysis technique was carried out in three stages: data reduction, data presentation, and conclusion drawing/verification. The results of the study indicate that political party administrators are more active before the general election, and political education for party administrators is very limited so the ability of party administrators is limited. The functions carried out by political parties are only based on instructions and the lack of political party activities outside the general election.